Students’ Grammatical Error Analysis in Writing Manual Procedure Text: A Study on SMK Negeri 1 Batusangkar - Amelia Putri Perdana; Dian Safitri (Journal of English Language Teaching, 2022)
This study aimed to find out grammatical errors and to reveal the most frequent grammatical error  in writing manual procedure text. The population of this study was the eleven graders of SMK Negeri 1 Batusangkar. The sample of this study was the eleven graders of AKL 1 and AKL 2. The sample was taken using purposive random sampling technique. The number of sample in this research was 42 students. The researcher used descriptive research design. The data were collected through a test. The finding was based on an analysis of the researcher and a rater. The rater was an English teacher of SMK Negeri 1 Batusangkar. After collecting the finding from the researcher and the rater, the researcher counted mean percentage of each grammatical error occurrence. According to likert scale, the interpretation of each grammatical error in writing manual procedure text was categorized as excellent, very good, good, and average. The final result showed that determiner error’s mean was 46,80% (average), noun error’s mean was 14,28% (good), verb error’s mean was 12,25% (good), conjunction error’s mean was 9,30% (very good), preposition error’s mean was 8,21% (very good), subject-verb agreement error’s mean was 7,15% (very good), and pronoun error’s mean was 2,15% (excellent). So, determiner error’s mean was the most frequent grammatical error in writing manual procedure text committed by eleven graders of SMK Negeri 1 Batusangkar academic year 2021/2022.